Reclutamiento y Selección del Personal en la Federación Deportiva de Los Ríos - Andrade Murillo, Leonardo Daniel (2019)
he Sports Federation of Los Ríos is an institution that generates sources of direct employment and indirectly in the city of Babahoyo and its surroundings, being the livelihood of several homes, it is thus that it can be highlighted that this institution provides employment opportunity to outsiders to their activity, in most cases they do not have enough education for their area of ​​action, but rather have the experience acquired over the years